Global Business and Competition Law in India - Ashok Chawla
Competition has become a driving force in today’s globalised world. Measures such as deregulation, liberalisation and privatisation are necessary, but not sufficient to ensure the efficient functioning of markets. The market distortions deprive markets of their ability to deliver efficient results, adversely impact growth and hurt the poor most of all through higher prices. Hence, there is a need for a robust competition law to protect and nurture the competitive process of the economy.